MODELING THE ECONOMIC AND HEALTH IMPACT OF INCREASING ELDERLY PHYSICAL ACTIVITY IN THE UNITED STATES. (11th November 2018) - Adam, A; Carlson, M
Abstract: Currently the vast majority of older adults in the United States (80 percent) suffer from at least one chronic condition (e.g., diabetes, hypertension, heart disease). Many of these health conditions are associated with physical inactivity, but only 34 percent of older adults currently meet the public health recommendation. Without knowing the potential economic and health impact of raising the number of older adults who meet the guidelines, policy makers and funders may not know the impact of PA strategies among many competing priorities. To capture all of these downstream effects, we developed a simulation model to quantify the health and economic impact of increasing PA in the in the current U.S. adult population (age: 40–50 years). This model is adapted from our validated two-stage computational simulation model representing the progression of an adult individual's health throughout the rest of her or her lifetime. It took in account two parallel levels: (1) Primary level: the daily caloric balance from energy intake and energy expenditure and (2) the Secondary level: yearly risks for associated chronic disease and health and economic impacts. Our study quantified the potential weight-related costs and health effects that might be averted by increasing the percentage of older adults who meet different recommended levels of physical activity (nationally and statewide), demonstrated that the possible savings substantially outweigh published costs of physical activity interventions, and identified the key drivers of these savings.